Competence, governance, and entrepreneurship : advances in economic strategy research - Foss, Nicolai (O.U.P. OxfordGB, 2000)
Brings together leading thinkers on competence, governance, and entrepreneurship to advance and stimulate economic strategy research. Shows that an innovative joint venture between these two main perspectives potentially leads to a new avenue of future research on strategic issues such as corporate growth, interfirm cooperation, and corporate entrepreneurship.